2015
DOI: 10.1094/pdis-03-14-0241-re
|View full text |Cite
|
Sign up to set email alerts
|

Use of PCR-RFLP Analysis to Monitor Fungicide Resistance inCercospora beticolaPopulations from Sugarbeet (Beta vulgaris) in Michigan, United States

Abstract: Genetic resistance to Quinone outside inhibitor (QoI) and benzimidazole fungicides may be responsible for a recent decline in efficacy of chemical control management strategies for Cercospora leaf spot (CLS) caused by Cercospora beticola in Michigan sugarbeet (Beta vulgaris) fields. The target genes and fungicide resistance mutations are known for these two fungicides. Based on this, two standard polymerase chain reaction restriction fragment length polymorphism (PCR-RFLP) assays were developed to detect the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Sanger DNA sequencing can be used to detect single nucleotide polymorphisms (SNPs), however, it can be expensive for multiple samples and there is a time delay to receive results. Allele-specific PCR ( Aoki et al, 2011 ), PCR-cleaved amplified polymorphic sequences (CAPS; Lesemann et al, 2006 ), and PCR-restriction fragment length polymorphism (PCR-RFLP; Rosenzweig et al, 2014 ) have all been used for rapid detection of fungicide resistance but are not quantitative. Real-time PCR assays have also been used to quantify fungicide resistance in B. graminis f. sp.…”
Section: Introductionmentioning
confidence: 99%
“…Sanger DNA sequencing can be used to detect single nucleotide polymorphisms (SNPs), however, it can be expensive for multiple samples and there is a time delay to receive results. Allele-specific PCR ( Aoki et al, 2011 ), PCR-cleaved amplified polymorphic sequences (CAPS; Lesemann et al, 2006 ), and PCR-restriction fragment length polymorphism (PCR-RFLP; Rosenzweig et al, 2014 ) have all been used for rapid detection of fungicide resistance but are not quantitative. Real-time PCR assays have also been used to quantify fungicide resistance in B. graminis f. sp.…”
Section: Introductionmentioning
confidence: 99%
“…Benzimidazole fungicides target and inhibit beta-tubulin in fungi, and the E198A target site mutation is known to confer high levels of resistance in C. beticola (Davidson et al 2006; Rosenzweig et al 2015; Shrestha et al 2020; Trkulja et al 2013). Therefore, we initially introduced the E198A beta-tubulin mutation into a benzimidazole-sensitive strain 16-1124 to establish a working gene editing method, which resulted in a benzimidazole-resistant phenotype (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this research, we indicated that these techniques are highly specific and prompt for detecting fungicide responsiveness. Rosenzweig et al (2015) developed PCR-RFLP to detect the G143A and E198A point mutations of the cytochrome b and β-tubulin genes in Cercospora leaf spot (CLS) caused by Cercospora beticola in Michigan sugar beet (Beta vulgaris) fields. The results showed that the PCR-RFLP assay was effective in detecting the presence of the G143A and E198A mutations in C. beticola from field populations in Michigan.…”
Section: Discussionmentioning
confidence: 99%